The Effect of ROA, DAR, and CR On Stock Returns in Retail Companies Listed on the IDX in the 2021-2024 Period - Mochamad Cece Farhan Siddiq; Erwin Budianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of profitability, leverage, and liquidity on stock returns in retail sector companies listed on the Indonesia Stock Exchange. Profitability is measured using Return on Assets, leverage is measured using the Debt to Asset Ratio, and liquidity is measured using the Current Ratio. This study applies a quantitative approach with a causal associative method. The data used are secondary data in the form of annual financial statements and stock price data of retail companies during the research period. The research sample was selected using purposive sampling based on specific criteria relevant to the study objectives. The data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, partial test, simultaneous test, and coefficient of determination. The results show that profitability has no significant effect on stock returns, indicating that a company’s ability to generate profit from its assets is not the main factor considered by investors. Leverage has a positive and significant effect on stock returns, suggesting that the proportional use of debt can be perceived as a positive signal by investors. Meanwhile, liquidity has a negative and significant effect on stock returns, indicating that excessively high liquidity may reflect inefficient management of current assets. Simultaneously, profitability, leverage, and liquidity affect stock returns, although stock return movements are also influenced by other factors outside the research model. These findings emphasize that investors should consider financial ratios comprehensively when assessing the stock prospects of retail companies.